Mental health status during COVID-19 pandemic in Fars Province, Iran: timely measures - Arash Mani; Ali Reza Estedlal; Mahsa Kamali; Seyede Zahra Ghaemi; Leila Zarei; Nasrin Shokrpour; Seyed Taghi Heydari; Kamran Bagheri Lankarani (BMC, 2020)
Abstract Background The current corona virus pandemic is acting as a stressor or trauma, which not only threats physical health status, but also threats mental health status and well-being of people. Currently, COVID-19 pandemic is a life-threatening unpredictable condition accompanied with a large number of uncertainties. The present study has mainly aimed to assess mental health and the relevant social factors during this pandemic in Fars province. Methods This cross-sectional study was performed on 922 participants in Fars province, Iran, using internet-based data collection technique. All the included participants filled out the General Health Questionnaire (GHQ-28). Moreover, demographic variables and some social factors were evaluated by asking some questions. All the participants were ensured of the confidentiality of the collected data, and willingly completed the questionnaire. Results Among the participants, there were 629 women (68.2%) and 293 men (31.2%). The mean age of the participants was 36.98 ± 11.08 years old. Four hundred twenty-five subjects (46.1%) obtained GHQ-28 scores above the cut-off point, and accordingly, they were suspected of having poor mental health statuses. Women, in comparison to men (OR = 2.034, 95%:1.62-3.28), and individuals aged < 50 years old, in comparison to those aged > 50 years old (OR: 4.01 95%:2.15-7.50), have poorer mental health statuses. Trusting on media, health authorities, and cooperation with policy makers, as well as having uncertainty on information about Coronavirus pandemic were also shown to be associated with poor mental health condition (P < 0.05). Conclusion The present study revealed that the number of those people with suspected poor mental health in Fars province significantly increased compared to a previous study using the same questionnaire. Furthermore, the participants who had less trust in media and policymakers were more prone to mental health problems. Therefore, it can be concluded that supporting people in these life-threatening pandemic crises is of great importance, so the policy makers and media must present reliable and valid information to people as soon as possible.